A sensitive and quantitative immunochromatographic assay for simultaneous detection of three stimulant laxatives in slimming food. (1st January 2023) - Chen, Sha; Guan, Tian; Qian, Zhenjie; Quan, Qiqi; Wang, Jin; Li, Xiangmei; Wu, Shaozong; Yan, Yiyong; Yao, Xiaojun; Zhang, Shiwei; Lei, Hongtao
Highlights: Novel haptens of three laxatives were rationally synthesized. The obtained monoclonal antibody demonstrated broad specificity. An immunochromatographic assay was developed for three laxatives. Abstract: Bisacodyl, sodium picosulfate and their metabolite bis-(p-hydroxyphenyl)-pyridyl-2-methane (BHPM) are clinically used to treat constipation. In this study, with the rational hapten design, a broad-specific and highly sensitive monoclonal antibody (mAb) was obtained with half of inhibitory concentrations of 0.16, 0.18 and 0.65 ng/mL for bisacodyl, sodium picosulfate and BHPM, respectively. Based on this mAb, a rapid and sensitive lateral flow immunochromatographic assay toward bisacodyl, sodium picosulfate and BHPM in slimming foods was developed. This method can qualitatively and quantitatively screen three stimulant laxatives with cut-off values of 3–6 ng/mL by naked eye and quantitative detection limits of 0.14–0.41 ng/mL by reader. The acceptable recoveries of spiked samples (78.00 %–120.12 %) and consistent results with liquid chromatography with tandem mass spectrometry (LC-MS/MS) in real sample detection confirmed the accuracy of the method. The established method provides a technique for multiplex, sensitive, fast, and on-site detection of three stimulant laxatives in slimming food.